The beastly feast - Goldstone, Bruce; Lent, Blair (New York : H. Holt, 1998)
All sorts of animals bring a variety of foods to share at a picnic: bears bring pears, parrots bring carrots, mosquitoes bring burritos, mice bring rice, and so on.
Keywords: Animals -- Fiction; Food -- Fiction; Stories in rhyme